Blockchain-based strategy for securing BGP routing and the design of the smart contract - Becci, Graciela (2024)
BGP Border Gateway Protocol is the Internet routing protocol,  responsible for the connectivity in the Internet. BGP guarantees Internet  connectivity between Autonomous Systems AS in a decentralised manner.  Since its origins, BGP has been based on mutual trust between ASes,  particularly with regard to route advertisements. However, in practice there  have been cases in which route advertisements have been blocked or diverted to  a non-intended destination, due to either operator’s inexperience or  intentionality, giving rise to Internet disruptions in the form of denial of service,  or route hijacking. Alternative solutions have been developed by official  organisations, leaders of the sector and researchers. However, none of these  solutions has been widely accepted. Blockchain as a distributed ledger, offers a  decentralised, peer-to-peer, and generally incorruptible chain of blocks of  records linked together by cryptographic hashes, guaranteeing the immutability  of each transaction. In this article, these blockchain characteristics are tha base  for the design of a BGP security strategy, which include as the main actors the  RIR and the ASes owners. This solution helps the border router operators to  retrieve information to build informed routing decisions for securing BGP  routing protocol .